OPTIMIZING THE KNOWLEDGE AND SKILLS OF COMMUNITY FIRST RESPONDERS THROUGH CPR MAT-BASED BLS TRAINING - Ninuk Dian Kurniawati; Yulis Setiya Dewi; Sriyono Sriyono; Arina Qona'ah; Erna Dwi Wahyuni; Vira Amellia; Karthikayini Krishnasamy; Harmayetty Harmayetty; Hakim Zulkarnain (Universitas Airlangga, 2026)
Introduction: Out-of-hospital cardiac arrest is a life-threatening emergency with a high mortality rate, often associated with delays in bystander response. Limited knowledge and inadequate skills in Basic Life Support among the general public remain major barriers to improving survival outcomes. Educational approaches using simple and practical media, such as CPR mats, have the potential to enhance community readiness in responding to cardiac emergencies. This community service activity aimed to improve the knowledge and skills of community members in performing BLS through the use of innovative CPR mat-based training. Methods: This community-based activity was conducted in Sukolilo Village in collaboration with the local Community Health Center (Puskesmas), involving 33 participants consisting of health cadres, PKK members (Family Welfare Movement), and community representatives. The intervention included structured education and simulation-based BLS training using a CPR mat. Program effectiveness was evaluated using pre- and post-tests, and the data were analyzed using the Wilcoxon signed-rank test. Results: Participants’ knowledge significantly improved after the intervention (p < 0.001), with the mean score increasing from 55.63 to 81.25 and a shift from predominantly poor to good knowledge levels. Practical BLS skills also showed significant improvement based on simulation assessments (p < 0.001), indicating enhanced ability to perform key procedures. Conclusion: CPR mat-based BLS education is effective in enhancing community knowledge, skills, and readiness to act as first responders in cases of cardiac arrest. This approach has strong potential to be implemented as a community-based strategy to improve early emergency response and survival outcomes. KEYWORDS basic life support; community first responders; CPR training; CPR mat-based training; universal health coverage